Analisis Eksistensi Dan Urgensi Hakikat Pendidikan Kewarganegaraan Dalam Kasus Penyalahgunaan Narkotika Di Kalangan Selebritas Indonesia - Jasmin Najwa Purmudi; Riska Dwi Savitri; Suhardi Suhardi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Drug abuse among celebrities in Indonesia is increasingly widespread, as evidenced by the number of news events both on television, national news websites and even in magazines. Drug abuse among Indonesian celebrities seems to be a place of escape from the problems of the life they live. Of course, drug abuse can be detrimental to oneself, causing negative stigma, loss of work for the celebrity and others, especially if it is done by celebrities who can be a bad example for the community. Celebrities have an influential position in changing people's perspectives and mindsets. Drug abuse is a social problem that can be caused by factors that influence it, one of which is a lack of understanding of civic education. The importance of understanding and learning civic education from elementary school to college can change awake behavior and shape character in accordance with the value of the precepts contained in Pancasila. Civic education can be one part of prevention in some relevant cases, for example drug abuse. This is in line with the importance of civic education which has been explained in the Indonesian Law No.20 of 2003 concerning the national education system, chapter 10 regarding the curriculum, article 37 paragraphs 1 and 2 which explain that Civics Education is one of the lessons that are mandatory in the curriculum of basic education, secondary education to higher education. Character building in civic education will become a habit so that it cannot be influenced by the surrounding environment, so that drug abuse among celebrities only becomes a mere entertainment spectacle by the community and cannot be imitated and only becomes a lesson for bad examples in society.